DIDACTIC POSSIBILITIES OF INTEGRATING TRANSVERSE COMPETENCIES IN THE PROCESS OF PROFESSIONAL TRAINING OF FUTURE ELEMENTARY TEACHERS - Zuvaydullayevna, Shakarova Nilufar (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to scientifically and pedagogically analyze the didactic possibilities of integrating transverse competencies into the professional training of future primary teachers, emphasizing their significance in fostering holistic educational development. Method: The research employed a combination of theoretical analysis, pedagogical observation, interviews, and experimental approaches to examine the role, content, and implementation strategies of transverse competencies within teacher education programs. Results: Findings revealed that integrating communicative, informational-literacy, creative, and reflexive competencies effectively enhances students’ professional readiness, interdisciplinary understanding, and capacity for innovative pedagogical thinking. The integrative approach demonstrated a significant impact on developing complex thinking skills and fostering creative problem-solving among future educators. Novelty: This study contributes to the pedagogical literature by establishing the didactic foundations for developing professional competencies through an integrated educational process, highlighting the transformative potential of transverse competencies in modern teacher education and proposing practical methods for their systematic implementation.